Comparison of different types of phacoemulsification tips. II. Morphologic alterations induced by multiple steam sterilization cycles with and without use of enzyme detergents. Issue 9 (September 2016) - Tsaousis, Konstantinos T.; Werner, Liliana; Reiter, Nicholas; Perez, Jesus Paulo; Li, He J.; Guan, Jia J.; Mamalis, Nick
Abstract : Purpose : To evaluate the alterations in the morphology and elemental composition of reusable phacoemulsification tips after cleaning and sterilization. Setting : John A. Moran Eye Center, Salt Lake City, Utah, USA. Design : Experimental study. Methods : For the main experiment, 2 types of reusable phacoemulsification needles were studied. One tip of each type underwent 1, 2, and 3 autoclave sterilizations with the use of detergents followed by thorough rinsing with sterile water between cycles. Another set of tips underwent the same procedure but without rinsing. Subsequently, phaco tips were examined through scanning electron microscopy and energy‐dispersive x‐ray spectroscopy to assess morphologic changes and surface deposits. In a second experiment, tips of 8 different types (both reusable and single use) underwent 10 sterilization autoclave cycles without detergents. Results : Residues, mostly comprised of carbon‐containing material, were found in extensive areas of tips that were sterilization with enzymes and without rinsing. Smaller and fewer residues were found in tips after sterilization with the use of enzymes and thorough rinsing. Tips that underwent autoclave sterilization without detergents had no bulky deposits on their surface; they mostly had thin layers of sodium and chloride or material discoloration. Conclusions : Rinsing the phaco tips significantly reduced the size and number of residues after use of enzymatic detergents. However, detergent residues were detected on phaco tip surfaces even after thorough rinsing with sterile water. No major noticeable changes were observed in either single‐use or reusable phaco tips after 10 cycles of sterilization without detergents. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.